Impact of Ligilactobacillus salivarius Li01 on benzo[a]pyrene-induced colitis, based on host-microbiome interactions in Mongolian gerbils - Huang, Yilun; Yang, Can; Fu, Bingmeng; Guo, Honggang; Chen, Yunxiang; Xu, Dengfeng (Frontiers in Nutrition, 2025)
BackgroundProbiotics supplementations have been regarded as an effective strategy for colitis treatment. However, the effect of Ligilactobacillus salivarius Li01 on benzo[a]pyrene (BaP)-induced colitis in Mongolian gerbils remains unclear. In this study, we leverage a BaP-induced model of colitis that exhibits significant remission following Ligilactobacillus salivarius Li01 intervention, to conduct an animal experiment that integrates histopathological assessment, inflammatory cytokines, 16S rRNA sequencing, targeted metabolomic profiling to investigate the relationship between Ligilactobacillus salivarius Li01, gut microbiota, and colitis.ResultsWe demonstrated that the improvements in colon histopathological assessment and inflammatory cytokines by Ligilactobacillus salivarius Li01 supplementation are accompanied by alterations in gut microbiota structure marked by increased abundance of strains with probiotic potential belonging to Bifidobacterium and Eubacterium_coprostanoligenes. Targeted metabolomic profiling analysis showed that Ligilactobacillus salivarius Li01 supplementation increases the concentration of acetic, propionic, butyric, and valeric acid. Correlation analysis showed that the alteration in the indicators associated with colitis is closely correlated to the changed microbial taxa and short-chain fatty acids (SCFAs).ConclusionThese data highlighted that Ligilactobacillus salivarius Li01 supplementation ameliorated the BaP-induced colitis, probably via modulating the structure of gut microbiota and promoting the production of SCFAs. Our findings provide preliminary evidence for a possible therapeutic strategy for the treatment of colitis based on host-microbiome interactions.